Combined aza-Michael and radical photopolymerization reactions for enhanced mechanical properties of 3D printed shape memory polymers. Issue 47 (25th October 2022) - Halbardier, Lucile; Goldbach, Emile; Croutxé-Barghorn, Céline; Schuller, Anne-Sophie; Allonas, Xavier
Abstract : A shape memory polymer formed from combined aza-Michael addition and radical photopolymerization. Abstract : 3D printed shape memory polymers (SMP) were formed by combining aza-Michael addition and light initiated radical polymerization. Amine consumption and acrylate conversion were monitored by 1 H-NMR and Fourier transform infrared spectroscopies. Dynamic mechanical analysis and cyclic thermomechanical tensile tests enabled direct observation of the polymer network changes. Increased homogeneity of the 3D network and enhanced SMP properties were achieved after the reaction between residual acrylate functions trapped in the vitrified medium with the secondary amines formed during the process. This allows the fabrication of shape memory objects by 3D printing.